Ghrelin regulates expression of the transcription factor Pax6 in hypoxic brain progenitor cells and neurons - Stoyanova, Irina I.; Klymenko, Andrii; Willms, Jeannette; Döppner, Thorsten R.; Tonchev, Anton B.; Lutz, David (MDPI, 2022)
The nature of brain impairment after hypoxia is complex and recovery harnesses different mechanisms, including neuroprotection and neurogenesis. Experimental evidence suggests that hypoxia may trigger neurogenesis postnatally by influencing the expression of a variety of transcription factors. However, the existing data are controversial. As a proof-of-principle, we subjected cultured cerebral cortex neurons, cerebellar granule neurons and organotypic cerebral cortex slices from rat brains to hypoxia and treated these cultures with the hormone ghrelin, which is well-known for its neuroprotective functions. We found that hypoxia elevated the expression levels and stimulated nuclear translocation of ghrelin’s receptor GHSR1 in the cultured neurons and the acute organotypic slices, whereas ghrelin treatment reduced the receptor expression to normoxic levels. GHSR1 expression was also increased in cerebral cortex neurons of mice with induced experimental stroke. Additional quantitative analyses of immunostainings for neuronal proliferation and differentiation markers revealed that hypoxia stimulated the proliferation of neuronal progenitors, whereas ghrelin application during the phase of recovery from hypoxia counteracted these effects. At the mechanistic level, we provide a link between the described post-ischemic phenomena and the expression of the transcription factor Pax6, an important regulator of neural progenitor cell fate. In contrast to the neurogenic niches in the brain where hypoxia is known to increase Pax6 expression, the levels of the transcription factor in cultured hypoxic cerebral cortex cells were downregulated. Moreover, the application of ghrelin to hypoxic neurons normalised the expression levels of these factors. Our findings suggest that ghrelin stimulates neurogenic factors for the protection of neurons in a GHSR1-dependent manner in non-neurogenic brain areas such as the cerebral cortex after exposure to hypoxia.
Keywords: Ghrelin; GHSR1; Hypoxia; Neurogenesis; Progenitor Cells; Transcription Factors